2017
DOI: 10.1515/popets-2017-0032
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Anti Ad-blockers in the Wild

Abstract: Abstract:The rise of ad-blockers is viewed as an economic threat by online publishers who primarily rely on online advertising to monetize their services. To address this threat, publishers have started to retaliate by employing anti ad-blockers, which scout for ad-block users and react to them by pushing users to whitelist the website or disable ad-blockers altogether. The clash between ad-blockers and anti ad-blockers has resulted in a new arms race on the Web. In this paper, we present an automated machine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 11 publications
1
15
0
3
Order By: Relevance
“…It is observed that there is a clash between ad blockers and anti ad blockers. An automated machine learning based approach is proposed to identify anti ad blockers that detect and react to ad blocking software users [29]. The goal is to enable ad blockers to bypass state-of-the-art anti ad blockers [30].…”
Section: Website Owners Preventing Ad Blockingmentioning
confidence: 99%
“…It is observed that there is a clash between ad blockers and anti ad blockers. An automated machine learning based approach is proposed to identify anti ad blockers that detect and react to ad blocking software users [29]. The goal is to enable ad blockers to bypass state-of-the-art anti ad blockers [30].…”
Section: Website Owners Preventing Ad Blockingmentioning
confidence: 99%
“…Scholars in the technological field research on how to develop either new ad blocking or anti ad blocking solutions (Backes, Bugiel, Styp-Rekowsky, & WiBfeld, 2017;Ikram & Kaafar, 2017a, 2017bJalba, Olteanu, & Draghici, 2016;Lashkari, Seo, Gil, & Ghorbani, 2017;Mughees, Qian, & Shafiq, 2017;Mughees, Qian, Shafiq, Dash, & Hui, 2016;Nithyanand et al, 2016;Tramèr, Dupré, Rusak, Pellegrino, & Boneh, 2018;Wills & Uzunoglu, 2016).…”
Section: Ad Blockermentioning
confidence: 99%
“…Apesar de a publicidade online ser ubíqua na atual economia digital (Rishab, 2016), as ferramentas adblocking, ao continuarem a crescer em popularidade (Nithyanad, 2016;Thomas, 2017;Umar, 2017), ameaçam dinâmicas de receitas publicitárias no sector dos media (Nithyanad, 2016). Daqui resulta que a exponenciação dos adblockers é vista como uma ameaça económica pelos editores online que primeiramente dependem da publicidade online para monetizar os seus serviços (Mughees, 2017). O aumento da popularidade dos adblockers levou a uma retaliação imediata por parte dos editores online a partir da utilização de ferramentas anti-adblocking capazes de detetar os utilizadores de adblockers e impedir o seu acesso aos conteúdos produzidos.…”
Section: Contextualizaçãounclassified
“…O aumento da popularidade dos adblockers levou a uma retaliação imediata por parte dos editores online a partir da utilização de ferramentas anti-adblocking capazes de detetar os utilizadores de adblockers e impedir o seu acesso aos conteúdos produzidos. É a designada nova Arms Race da Internet (Umar, 2017;Ikram, 2017;Nithyanad, 2016;Mughees, 2017).…”
Section: Contextualizaçãounclassified
See 1 more Smart Citation